(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Technological advancements that do not impact the range of picture operations, the availability of advanced image alteration software, or image management have increased the availability of images in a wide variety of applications. The demand for storage space and communication bandwidth continues to outstrip the existing capacity even if there has been technological advancements in transmission and storage. This means that compressing images is a useful strategy. We explore classic lossless methods, such as Run-Length Encoding (RLE) and Huffman coding, and lossy techniques like JPEG and JPEG2000, analyzing their performance in preserving image quality while minimizing file size. Moreover, we delve into advanced methods driven by machine learning, particularly deep learning-based approaches such as convolution neural networks (CNNs) and autoencoders, which have shown promising results in achieving higher compression ratios with less perceptible quality loss. The paper also addresses key challenges in image compression, including compression efficiency, artifact reduction, and balancing quality preservation with compression ratio. Furthermore, we review the role of compression in domain-specific applications, such as medical image analysis, remote sensing, and video surveillance, where both lossless accuracy and lossy efficiency must be carefully optimized. Finally, we highlight emerging trends, including hybrid approaches combining traditional methods with deep learning, and their potential to shape the future of image compression. This paper aims to provide insights into the current state-of-the-art in image compression, offering valuable guidance for researchers, practitioners, and engineers seeking to enhance image storage and transmission techniques in various applications.